Innovahubs local stakeholder participatory activities: Participatory workshops with all relevant local actors, including NARES, NGOs, farmers and their associations and private sector representatives - Diaz Espinosa, Anabell; Borrayo, Andrea; Torres, Suelen; Loon, Jelle van (Bioversity International and the International Center for Tropical Agriculture, 2023)
One of the main objectives of the Innovahubs model promoted within the regional Initiative AgriLAC Resiliente is to provide spaces for collaborative learning by promoting the exchange and participation of actors from the different regions of intervention in Honduras and Guatemala. The participatory workshops developed are one of the fundamental pillars to promote the identification, knowledge, exchange, and participation of local actors, allowing the connection between individuals and public and private civil associations, to add value to sustainable agricultural management solutions, sensitive to nutrition and adapted to the context from the climatic point of view. Typical of these events is their focus to stimulate spaces that enhance the learning process, guaranteeing the effectiveness of the actions and seeking unity and integrality of social interventions aiming to decrease disarticulated action. In this sense, in 2023, events of different types were held with the intention of promoting interaction and participatory exchange among network stakeholders such as farmers, partners, collaborators, students, researchers, among others; where through selection processes, workshops, training courses and workshops for the exchange of experiences, the stakeholders dialogued, interacted and learned about the experience of others in different areas and contexts; in order to identify areas of consensus for decision-making or the establishment of joint lines of action. This report gives an overview of the different workshops held in Guatemala and Honduras, aiming to detect learning needs and setting up a participatory training plan in the Innovahubs.